Endogenous Intellectual Property Rights and North-South Trade - Andreas Schäfer; Maik T. Schneider (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Even though most countries have agreed to a harmonization of intellectual property rights by signing the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), there is still much dispute about the optimal level of protection of intellectual property rights in the world. Particularly some developing countries argue that the high protection standards in TRIPS benefit the North at the expense of their own welfare. On the other hand, many developed countries, mostly located in the northern hemisphere, have the impression that the legal practice in the South leaves much to be desired. In this paper, we provide a framework unifying micro- and macroeconomic perspectives which is capable to analyze the North's and the South's incentives for providing IPR protection. This research suggests that current IPR policies are conducive for economic growth. Moreover, the South may experience welfare gains if the research productivity of the North is not too low.
Keywords: F10; O30; O34; F13; 330; Endogenous Growth; Intellectual Property Rights; Trade; Dynamic Game